Formation mechanism of Ruddlesden–Popper faults in compressive-strained ABO3 perovskite superlattices. Issue 48 (8th December 2021) - Qi, Haoyuan; Chen, Xiaodan; Benckiser, Eva; Wu, Meng; Cristiani, Georg; Logvenov, Gennady; Keimer, Bernhard; Kaiser, Ute
Abstract : In an oxide perovskite superlattice, Ruddlesden–Popper faults were found to form via Shockley partials bounded by basal plane stacking faults. The formation of such Ruddlesden–Popper faults could facilitate the relaxation of compressive strain. Abstract : Ruddlesden–Popper (RP) faults have emerged as a promising candidate for defect engineering in epitaxial ABO3 perovskites. Functionalities could be fine-tuned by incorporating RP faults into ABO3 thin films and superlattices. However, due to the lattice expansion at AO–AO interfaces, it is generally believed that RP faults are only energetically favorable under tensile strain. Contrary to this common cognition, here we present that compressive strain must be regarded as an alternative driving force for creating RP faults. Unlike the conventional perovskite-to-rock-salt transition, the RP faults originated from Shockley partial dislocations bounded by stacking faults on the basal plane. The edge-type partials gave rise to strain relaxation, facilitating the formation of RP faults under compressive strain. We envisage that our results will give new insights into the rational design and defect engineering in epitaxial-strained ABO3 perovskites.